2011
DOI: 10.1108/00021461111128156
|View full text |Cite
|
Sign up to set email alerts
|

The influence of GM crop adoption on the profitability of farms operated by young and beginning farmers

Abstract: Purpose -The purpose of this paper is to assess the impacts of GM crop adoption on the profitability of farms operated by young and/or beginning farmers and ranchers (YBFR). Design/methodology/approach -This research uses weighted quantile regression analysis in conjunction with 2004-2006 Agricultural Resource Management Survey to evaluate the impact of GM crop adoption on financial performance of farms operated by YBFR. The methodology employed in this study corrects for the simultaneity of technology adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…Another contribution of this article is the empirical evidence that beginning farmers were more likely to adopt VA technologies when compared to experienced operators (p<0.1). This result is consistent with the beginning farmer literature that showed that beginning farmers tend to be motivated to replace traditional agricultural processes with new technologies (Detre et al. , 2011).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 86%
See 3 more Smart Citations
“…Another contribution of this article is the empirical evidence that beginning farmers were more likely to adopt VA technologies when compared to experienced operators (p<0.1). This result is consistent with the beginning farmer literature that showed that beginning farmers tend to be motivated to replace traditional agricultural processes with new technologies (Detre et al. , 2011).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 86%
“…Another contribution of this article is the empirical evidence that beginning farmers were more likely to adopt VA technologies when compared to experienced operators ðp < 0:1Þ. This result is consistent with the beginning farmer literature that showed that beginning farmers tend to be motivated to replace traditional agricultural processes with new technologies (Detre et al, 2011). One explanation may be that the adoption of VA technologies among beginning farmers may be seen as an optimization strategy to address limited access to land, while experienced farmers may have already reached optimized economies of scale and land access (Katchova and Dinterman, 2018).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 85%
See 2 more Smart Citations
“…Both NFI and net returns per unit (NRU) of milk sold were used as measures of financial performance in El-Osta and Johnson (1998), and performed as dependent variables in regression models. Similarly, Detre et al (2011) used NFI and ROA as measures of financial performance and fitted them independently in regression. A derivative work is Mishra et al (2012) which applied the idea of DuPont expansion and used net profit margins, ATR and total assets to net worth ratios in SUR models to identify factors influencing agricultural profitability.…”
Section: Conceptual Modelmentioning
confidence: 99%